EDUCATIONAL MARKETING STRATEGIES IN INTEGRATED ISLAMIC JUNIOR HIGH SCHOOL - Salma Nurillah; Heriawan, Endang; Sururi (Universitas Negeri Surabaya, 2024)
This study analyzes the implementation of education marketing strategies in an integrated Islamic junior high school using the marketing mix theory. A descriptive qualitative approach was employed to collect data through in-depth interviews and observations. The research subjects consisted of school leaders, teachers, school committee representatives, and parents. The collected data underwent analysis with the assistance of ATLAS.ti software. The findings revealed that the school's marketing strategy encompasses market segmentation, targeting, and positioning that are customized to product characteristics, consumer demographics, and institutional capacity. The marketing strategy is anchored by the 7P framework, encompassing product, price, place, promotion, people, physical evidence, and process. The analysis revealed that the school demonstrated a predilection for conventional promotional strategies, such as socialization to proximate primary schools and word-of-mouth marketing. The effectiveness of marketing strategies is influenced by a multitude of internal and external factors, including the decline in public interest in education due to the pandemic. This study posits that collaboration with primary schools emerges as the most efficacious strategy for enhancing education marketing. The study's findings offer strategic recommendations for educational institutions seeking to enhance their marketing efforts, with the aim of increasing student enrollment and enhancing their reputation.